The Relationship Between Nutritional Status And The Incidence Of Pneumonia In Adult Patients At Royal Prima RSu Medan - Yuliani Mardiati Lubis; Ravina Putri Indra Siregar; Andika Zayani Tambunan (Jurnal EduHealth, 2023)
Pneumonia is a common disease with a high global prevalence. Hospitalization rates for elderly pneumonia patients are five times higher than those for adult patients. Pneumonia has lasting consequences, including diminished lung function. As a result, pneumonia remains a critical public health issue in Indonesia. A person's susceptibility to illness may be affected by their nutritional state. It is easier to become sick from malnutrition-related immune system problems. The effects of malnutrition and infection on one another are two-way. People who are malnourished are more susceptible to catching pneumonia, and the latter may worsen their condition. The purpose of this research was to examine the association between patients' nutritional state and the occurrence of pneumonia at RSU Royal Prima Medan, an adult hospital. This investigation is a retrospective, analytical study. Adult patients with pneumonia who were seen at RSU Royal Prima Medan during the months of October and December 2022 made up the study population. Utilizing the Slovin algorithm for simple random sampling, we were able to collect data from 45 participants for analysis utilizing univariate and bivariate methods. The majority of patients diagnosed with pneumonia at RSU Royal Prima Medan were male, older than 40 years old, and had clinical signs of chest discomfort. At RSU Royal Prima Medan, 19 patients with pneumonia had a normal nutritional state and 26 had a bad nutritional status. Adult patients at RSU Royal Prima Medan have a p-value < 0.05 correlation between their dietary health and the occurrence of pneumonia.